Ideals of joint decision making in clubhouse communities - Mäntysaari, Kati; Stevanovic, Melisa; Weiste, Elina; Paananen, Jenny; Lindholm, Camilla (American Psychological Association, 2025)
Objective: This article explores the ideological dilemmas of decision making identified in members’ and staff’s talk in Clubhouse communities. Method: The data are drawn from a corpus of 10 video-recorded focus group interviews with Clubhouse members and staff, which were collected at five Finnish Clubhouses in 2020. The method used is discursive psychology, and the analysis identifies interpretative repertoires and ideological dilemmas. Results: Clubhouse members and staff express diverse opinions regarding decision making at the Clubhouse. We identified six interpretative repertoires and three ideological dilemmas between these repertoires. The first dilemma deals with participation and efficiency, advancing the idea that everybody should be allowed to participate in decision making, but the decision making should be efficient. The second dilemma regards the passivity or activity of the participants, suggesting that decision-makers should be allowed to be themselves, but participation in decision making requires activity. The third dilemma is associated with power structures in decision making, proposing that joint decision making requires active resistance against power structures, but these structures are both inexorable and partially necessary. Conclusions and Implications for Practice: In introducing a discursive perspective to joint decision making in the Clubhouse community, this study makes visible the conflicting ideals of decision making. The acknowledgment of these dilemmas can guide interventions aiming at improving genuinely participatory joint decision-making practices at the Clubhouse.
Impact and Implications: The study shows that Clubhouse members and staff have conflicting ideals about joint decision making at the Clubhouse. The staff’s views constitute a potential risk, as they highlight the active role of members and associate efficient decision making with the inexorability of power structures. By making the conflicting ideals visible, the study can inform interventions to improve joint decision making in the Clubhouse community.